Both Freshly Prepared and Frozen-Stored Amniotic Membrane Cells Express the Complement Inhibitor CD59 - Ágnes Füst; Éva Pállinger; Adrienn Stündl; Eszter Kovács; László Imre; Sára Tóth; János Németh (The Scientific World Journal)
Amniotic membrane proved to be very effective tool in the treatment of a number of ocular surface diseases. The amniotic membrane, however, has to be stored before its transplantation onto the ocular surface followed by mandatory serologic control in order to exclude the transmission of certain viruses. Therefore it is most important to study if cryopreservation of the membrane affects cell surface expression of the molecules. We measured cell surface expression of CD59, a membrane-bound complement inhibitor on the cells of freshly prepared and cryopreserved amniotic membrane. Cells of amniotic membrane were separated mechanically. Epithelial and mesenchymal cells were identified by the intracellular expression of nanog and the cell surface ICAM1 positivity, respectively. Multicolor flow cytometric immunophenotyping was used for determination of the CD59 expression. CellQuest-Pro software program (Becton Dickinson) was used both for measurements and analysis. CD59-positive cells could be detected in all investigated samples and in all investigated cell types, although the expression level of CD59 differed. CD59 was expressed both on freshly prepared and frozen-stored samples. Higher level of CD59 was detected on ICAM1+ mesenchymal cells than on nanog+ epithelial cells. Our findings indicate that amniotic membranes maintain their complement inhibiting capacity after cryopreservation.